Tolerogenic dendritic cell-regulatory T cell interaction and the promotion of transplant tolerance - Thomson, Angus W. (2009)
Evidence has accumulated that targeting of donor alloantigen to quiescent dendritic cells (DC) in situ or adoptive DC therapy is associated with the expansion or induction of regulatory T cells (T reg) in experimental organ transplantation. These Treg can mediate suppression of anti-donor T effector cell responses and promote allograft tolerance. In addition, Treg can exert reciprocal, inhibitory effects on DC that maintain their tolerogenic properties. Several groups have exploited DC to expand alloAg-specific Treg in vitro, followed by adoptive transfer of the Treg to graft recipients, an approach that holds promise for tolerogenic cell therapy in clinical cell and organ transplantation.